HUBUNGAN TEKNIK MENYUSUI DAN PRAKTEK BREAST CARE DENGAN KEJADIAN BENDUNG ASI - Rafita Dewi; Yoga Tri Wijayanti; Yetti Anggraini (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2017)
According to the Indonesia Demographic and Health Survey 2012-2013 shows that 55% of breastfeeding mothers in Indonesia have swollen breasts and mastitis, possibly due to lack of breast care during pregnancy and improper breastfeeding techniques. This study aims to determine the relationship between breastfeeding techniques and breast care practices on the incidence of breast engorgement at Midwifery Private Practice Ponirah Margorejo Metro Metro South Metro District 2017. Sampling in this study is Saturated Sampling. Data collection method is observation by using tool checklist. Data analysis used was univariate analysis and bivariate analysis with chi-square stratic test. The result of this research is got the characteristic of respondent average 20-30 years old and parity average is parity one. Univariate analysis showed that 14 breastfeeding respondents and 23 (65,7%) respondents had performed breastfeeding technique correctly and 25 (71,5%) respondents had done breast care practice correctly. So there is correlation between breastfeeding technique and breast care practice with the incidence of breast engorgement because less than p-value (0,05), hence the result of the analysis can be concluded that there is influence of breastfeeding technique and breast care practice with the incidence of milk dam. Breast engorgement is a very agitating complaint activity of postpartum mothers, so it is necessary also supervision and attention of midwives to handle the implementation of breastfeeding techniques and practice of breast care.